Profiling functional networks identify activation of corticostriatal connectivity in ET patients after MRgFUS thalamotomy - Jiaji Lin; Xiaopeng Kang; Jiayou Zhou; Dekang Zhang; Jianxing Hu; Haoxuan Lu; Longsheng Pan; Xin Lou (NeuroImage: Clinical, 2024)
Background: MR-guided focused ultrasound (MRgFUS) thalamotomy is a novel and effective treatment for medication-refractory tremor in essential tremor (ET), but how the brain responds to this deliberate lesion is not clear. Objective: The current study aimed to evaluate the immediate and longitudinal alterations of functional networks after MRgFUS thalamotomy. Methods: We retrospectively obtained preoperative and postoperative 30-day, 90-day, and 180-day data of 31 ET patients subjected with MRgFUS thalamotomy from 2018 to 2020. Their archived resting-state functional MRI data were used for functional network comparison as well as graph-theory metrics analysis. Both partial least squares (PLS) regression and linear regression were conducted to associate functional features to tremor symptoms. Results: MRgFUS thalamotomy dramatically abolished tremors, while global functional network only sustained immediate fluctuation within one week after the surgery. Network-based statistics have identified a long-term enhanced corticostriatal subnetwork by comparison between 180-day and preoperative data (P = 0.019). Within this subnetwork, network degree, global efficiency and transitivity were significantly recovered in ET patients right after MRgFUS thalamotomy compared to the pre-operative timepoint (P < 0.05), as well as hemisphere lateralization (P < 0.001). The PLS main component significantly accounted for 33.68 % and 34.16 % of the total variances of hand tremor score and clinical rating scale for tremor (CRST)-total score (P = 0.037 and 0.027). Network transitivity of this subnetwork could serve as a reliable biomarker for hand tremor score control prediction at 180-day after the surgery (β = 2.94, P = 0.03). Conclusion: MRgFUS thalamotomy promoted corticostriatal connectivity activation correlated with tremor improvement in ET patient after MRgFUS thalamotomy.